Manufacturing method of grain-oriented electrical steel sheet
By employing specific component compositions and controlled heating processes, the method addresses the decrease in magnetic flux density during rapid heating in electromagnetic steel plates, achieving low iron loss and maintaining magnetic flux density through controlled heating rates and atmospheres.
Patent Information
- Application Number
- JP2022541800
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-28
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2042-03-28
AI Technical Summary
Existing methods to reduce iron loss in directional electromagnetic steel plates through rapid heating during decarburization grilling result in a decrease in magnetic flux density.
A method involving specific component compositions and heating processes, including gradual heating at controlled temperature ranges and atmospheres, to maintain magnetic flux density while reducing iron loss, using C: 0.002 ~ 0.10mass%, Si: 2.0 ~ 8.0mass%, Mn: 0.005 ~ 1.0mass%, and inhibitor-forming components, with controlled heating rates and insulating coatings.
Achieves low iron loss without a decrease in magnetic flux density by controlling the heating process to maintain the Goss orientation of crystal grains, using controlled heating rates and atmospheres.
Smart Images

Figure 0007623636000001 
Figure 0007623636000002 
Figure 0007623636000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a grain-oriented electrical steel sheet having low core loss and high magnetic flux density. [Background technology]
[0002] Grain-oriented electrical steel is a soft magnetic material used as the core material for transformers and generators, and has an easy magnetization axis of iron. <001> The characteristic of this steel is that it has a crystal structure with a highly aligned orientation in the rolling direction of the steel sheet. This type of texture causes secondary recrystallization during the finish annealing process of the grain-oriented electrical steel sheet manufacturing process, resulting in a crystal structure with a Goss orientation {110} <001> It is formed by preferentially growing crystal grains in the same orientation.
[0003] To induce the secondary recrystallization, a technique using fine precipitates called inhibitors is generally used. For example, Patent Document 1 discloses a method using MnS or MnSe as an inhibitor, and Patent Document 2 discloses a method using AlN or MnS as an inhibitor, both of which have been put into practical use industrially. Although these methods using inhibitors require heating the slab to an extremely high temperature of 1300°C or higher, they are very effective methods for stably inducing secondary recrystallization.
[0004] As techniques for enhancing the action of these inhibitors, Patent Document 3 discloses a method of adding Pb, Sb, Nb, or Te, and Patent Document 4 discloses a method of adding Zr, Ti, B, Nb, Ta, V, Cr, and Mo. Furthermore, Patent Document 5 proposes a method in which acid-soluble Al (sol.Al) is added to a steel material at 0.010 to 0.060%, the slab heating temperature is kept low, and nitriding is performed in an appropriate atmosphere in the decarburization annealing process, thereby precipitating (Al,Si)N during secondary recrystallization in finish annealing and using it as an inhibitor.
[0005] On the other hand, a technology for developing Goss-oriented grains by secondary recrystallization using a steel material that does not contain inhibitor-forming components is disclosed in Patent Document 6 and the like. This technology is a technology for secondary recrystallization of grains having Goss orientation without using inhibitors by eliminating impurities such as inhibitor-forming components as much as possible and manifesting the grain boundary misorientation angle dependency of the grain boundary energy of the crystal grain boundary during primary recrystallization, and the effect is also called texture inhibition. This method has great advantages in terms of cost and production, such as no need for a process for purifying inhibitor-forming components, no need for high-temperature finish annealing, and no need for fine dispersion of inhibitors, so no need for high-temperature slab heating that is essential for dissolving inhibitor-forming components.
[0006] Furthermore, to improve the performance of transformers, it is necessary to reduce no-load loss (energy loss), and it is essential that the steel sheet material that forms the iron core has low iron loss.Methods known to be effective in reducing iron loss in grain-oriented electrical steel sheets include increasing the silicon content, reducing sheet thickness, improving the crystal orientation, applying tension to the steel sheet, smoothing the steel sheet surface, and refining the grains of the secondary recrystallized structure.
[0007] Among the above methods, a method has been proposed for improving the primary recrystallization texture by rapid heating during decarburization annealing as a technique for refining secondary recrystallized grains. For example, Patent Document 7 discloses a technique for obtaining a grain-oriented electrical steel sheet with low iron loss by limiting the amount of N as AlN in the hot-rolled sheet to 25 massppm or less and heating to 700°C or higher at a heating rate of 80°C / s or more during decarburization annealing. Patent Document 8 also discloses a technique for obtaining a grain-oriented electrical steel sheet with low iron loss by decarburizing annealing a cold-rolled sheet that has been rolled to the final sheet thickness. H2O / P H2 This technique provides a grain-oriented electrical steel sheet with low iron loss by rapidly heating to a temperature of 700° C. or higher at a rate of 100° C. / s or higher in a non-oxidizing atmosphere with a modulus of 0.2 or less. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Special Publication No. 51-013469 [Patent Document 2] Special Publication No. 40-015644 [Patent Document 3] Special Publication No. 38-008214 [Patent Document 4] Japanese Patent Application Publication No. 52-024116 [Patent Document 5] Japanese Patent Application Publication No. 03-002324 [Patent Document 6] JP 2000-129356 A [Patent Document 7] Japanese Patent Application Publication No. 10-130729 [Patent Document 8] Japanese Patent Application Publication No. 07-062436 Summary of the Invention [Problem to be solved by the invention]
[0009] However, in the techniques disclosed in the above Patent Documents 7 and 8, rapid heating during decarburization annealing reduces iron loss, but there is a problem in that the magnetic flux density also decreases. Therefore, an object of the present invention is to propose a method for producing a grain-oriented electrical steel sheet with low iron loss and high magnetic flux density by preventing the decrease in magnetic flux density caused by rapid heating during decarburization annealing when a steel material containing inhibitor-forming components is used, thereby preventing the decrease in magnetic flux density caused by rapid heating during decarburization annealing. [Means for solving the problem]
[0010] The inventors conducted extensive research into the cause of the decrease in magnetic flux density due to rapid heating during the decarburization annealing. As a result, they discovered that when increasing the temperature rise rate during the heating process of the decarburization annealing, the temperature range in which secondary recrystallization occurs during the finish annealing is slowly heated, and only the crystal grains with the Goss orientation are allowed to grow, thereby realizing low iron loss without causing a decrease in magnetic flux density, and thus developed the present invention.
[0011] The present invention based on the above findings provides a method for producing a steel material having a composition comprising: 0.002-0.10 mass% C, 2.0-8.0 mass% Si, and 0.005-1.0 mass% Mn; and further comprising, as inhibitor-forming components, components of the following group A or group B, with the balance being Fe and unavoidable impurities. The steel material is heated to a temperature of 1300°C or higher and 1400°C or lower, hot-rolled to obtain a hot-rolled sheet, and the hot-rolled sheet is annealed, followed by one cold rolling or two or more rolling steps including intermediate annealing. The present invention proposes a method for producing a grain-oriented electrical steel sheet, which comprises cold rolling the steel sheet to a final thickness, subjecting the cold rolled sheet to decarburization annealing which also serves as primary recrystallization annealing, applying an annealing separator to the surface of the steel sheet, subjecting the steel sheet to finish annealing, and then forming an insulating coating by rapidly heating the steel sheet between 500 and 700°C at a rate of 100 to 1000°C / s in the heating process of the decarburization annealing, and then gradually heating the steel sheet between 860 and 970°C in the heating process of the finish annealing for at least 10 hours at a heating rate of 0.5 to 4.0°C / hr. Note Group A: Al: 0.010-0.050 mass% and N: 0.003-0.020 mass% Group B: Al: 0.010-0.050 mass%, N: 0.003-0.020 mass%, Se: 0.003-0.030 mass% and / or S: 0.002-0.030 mass%
[0012] The steel material used in the method for producing grain-oriented electrical steel sheet of the present invention is characterized in that, in addition to the above-mentioned chemical composition, it further contains at least one of Ni: 0.01-1.50 mass%, Cr: 0.01-0.50 mass%, Cu: 0.005-1.000 mass%, P: 0.005-0.500 mass%, Sb: 0.005-0.500 mass%, Sn: 0.005-0.500 mass%, Bi: 0.005-0.500 mass%, Mo: 0.005-0.500 mass%, Nb: 0.0010-0.0100 mass%, Ta: 0.001-0.010 mass%, and Ti: 0.001-0.0100 mass%.
[0013] The method for producing a grain-oriented electrical steel sheet of the present invention is characterized in that in any step after the above-mentioned cold rolling, grooves are formed on the surface of the steel sheet in a direction intersecting the rolling direction to perform magnetic domain refinement treatment.
[0014] The method for producing a grain-oriented electrical steel sheet of the present invention is characterized in that the surface of the steel sheet covered with the insulating coating is irradiated with an electron beam or a laser beam in a direction intersecting with the rolling direction to perform a magnetic domain refinement treatment. Effect of the Invention
[0015] According to the present invention, the heating rate in the temperature range in which secondary recrystallization occurs in finish annealing is optimized, and secondary recrystallization of crystal grains that are deviated from the Goss orientation is suppressed. Therefore, even when rapid heating is performed during decarburization annealing, it is possible to produce a grain-oriented electrical steel sheet with low iron loss without incurring a decrease in magnetic flux density. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] First, the experiments that led to the development of the present invention will be described. A steel slab containing C: 0.030 mass%, Si: 3.0 mass%, Mn: 0.014 mass%, Al: 0.038 mass%, N: 0.011 mass%, Se: 0.022 mass%, and S: 0.009 mass%, with the balance being Fe and unavoidable impurities, was produced by a continuous casting method. The slab was then heated to a temperature of 1350 ° C, and hot rolled to finish into a hot rolled sheet with a thickness of 2.4 mm. The hot rolled sheet was then subjected to hot rolled sheet annealing at 1100 ° C × 30 seconds, and then subjected to a first cold rolling to an intermediate sheet thickness of 1.8 mm, and then subjected to intermediate annealing at 1020 ° C × 100 seconds, and then subjected to a second cold rolling with a reverse rolling mill to finish into a cold rolled sheet with a final sheet thickness of 0.23 mm. Next, the cold-rolled sheet was subjected to decarburization annealing, which also served as primary recrystallization annealing, at 880°C for 60 seconds in a 50vol%H2-50vol%N2 wet atmosphere. At this time, the heating rate between 500 and 700°C was set to two levels, 30°C / s and 200°C / s. Next, an annealing separator mainly composed of MgO was applied to the surface of the steel sheet, and the steel sheet in a coiled state was heated to 900°C at 25°C / hr in an N2 atmosphere, held at the above temperature for 20 hours, then heated to 970°C at 25°C / hr, and further heated to 1180°C at 25°C / hr in a mixed atmosphere of H2:50vol%-N2:50vol%, and held at the above temperature for 5 hours in an H2 atmosphere to perform finish annealing for purification.
[0017] Test pieces were taken from the steel sheets after the final annealing, and the iron loss W 17 / 50 The iron loss (iron loss when excited at 1.7 T at a frequency of 50 Hz) and magnetic flux density B8 (magnetic flux density at a magnetizing force of 800 A / m) were measured using the method described in JIS C 2550. Test pieces were taken from three locations, namely, both ends and the center of the product coil, and the worst (highest) iron loss value and the lowest (worst) magnetic flux density value were taken as representative values for that coil. The results of the above measurements are shown in Table 1 below. It can be seen that when the heating rate between 500 and 700°C in the decarburization annealing heating process is 200°C / s, the iron loss value tends to improve compared to a heating rate of 30°C / s, but the magnetic flux density tends to decrease.
[0018] [Table 1]
[0019] Therefore, experiments were carried out in which the heating rate between 500 and 700°C in the decarburization annealing process was set to 200°C / s (constant), and the heating rate between 860 and 970°C in the final annealing process was changed as shown in Table 2. 17 / 50 and magnetic flux density B8 were measured. The results of the above measurements are shown in Table 2 below. From these results, it was found that there is a suitable range for the temperature rise rate in the final annealing that can achieve both low iron loss and high magnetic flux density, specifically, 0.5 to 4.0°C / hr.
[0020] [Table 2]
[0021] As described above, the reason why the iron loss reduction effect of rapid heating in decarburization annealing can be achieved without causing a decrease in magnetic flux density by optimizing the heating rate between 860 and 970°C in final annealing has not yet been fully elucidated, but the inventors believe it to be as follows. When the heating rate of the decarburization annealing is increased, the number of recrystallized grains in the primary recrystallized structure and their neighboring grains increases. As a result, the increased number of primary recrystallized grains in the Goss orientation and their neighboring grains undergo secondary recrystallization in the final annealing, resulting in a fine-grained secondary recrystallized structure. Here, as proposed by the present invention, when the temperature is slowly heated at 0.5 to 4.0 ° C / hr in the temperature range of 860 to 970 ° C, the grain growth of the Goss oriented grains relative to their neighboring grains becomes dominant, the orientation sharpness of the secondary recrystallized structure increases, and the magnetic flux density B8 increases. On the other hand, when the heating rate is less than 0.5 ° C / hr, the difference in grain growth between the Goss oriented grains and their neighboring grains is small, and the orientation sharpness of the secondary recrystallized structure decreases. On the other hand, when the heating rate exceeds 4.0 ° C / hr, the growth rate of both the Goss orientation and its neighboring grains increases significantly, and it is believed that the orientation sharpness of the secondary recrystallized structure also decreases. The present invention has been developed based on the above novel findings.
[0022] Next, the chemical composition of the steel material (slab) used in the production of the grain-oriented electrical steel sheet of the present invention will be described. C: 0.002 to 0.10 mass% If the C content is less than 0.002 mass%, the grain boundary strengthening effect of C is lost, and cracks may occur in the slab, causing problems during manufacturing and surface defects. On the other hand, if the C content exceeds 0.10 mass%, it becomes difficult to reduce the C content to 0.005 mass% or less, at which magnetic aging does not occur during decarburization annealing. Therefore, the C content is set to a range of 0.002 to 0.10 mass%, and preferably to a range of 0.010 to 0.080 mass%.
[0023] Si: 2.0~8.0mass% Silicon is an essential component for increasing the resistivity of steel and reducing iron loss, and if it is less than 2.0 mass%, the above effect is insufficient, while if it exceeds 8.0 mass%, the workability decreases and rolling becomes difficult. Therefore, the silicon content is set to the range of 2.0 to 8.0 mass%, and preferably to the range of 2.5 to 4.5 mass%.
[0024] Mn: 0.005 to 1.0 mass% Mn improves the hot workability of steel, and must be contained at 0.005 mass% or more. On the other hand, if it exceeds 1.0 mass%, the magnetic flux density of the product sheet decreases. Therefore, the Mn content is set to the range of 0.005 to 1.0 mass%, and preferably to the range of 0.02 to 0.20 mass%.
[0025] As the components other than C, Si, and Mn, it is necessary to contain inhibitor-forming components necessary for developing secondary recrystallization during finish annealing. Specifically, when an AlN-based inhibitor is used as the inhibitor, it is necessary to contain Al and N in the ranges of Al: 0.010-0.050 mass%, and N: 0.003-0.020 mass%, respectively. The ranges of Al: 0.013-0.025 mass%, and N: 0.005-0.010 mass% are preferable. In addition, an AlN-based inhibitor and an MnS·MnSe-based inhibitor may be used in combination, and in that case, it is necessary to contain Al: 0.010-0.050 mass%, N: 0.003-0.020 mass%, S: 0.002-0.030 mass%, and / or Se: 0.003-0.030 mass%. Preferably, the ranges are Al: 0.013-0.025 mass%, N: 0.005-0.010 mass%, S: 0.004-0.015 mass%, and / or Se: 0.005-0.020 mass%. If the respective contents are less than the lower limit values, the inhibitor effect is not sufficiently obtained, whereas if they exceed the upper limit values, the inhibitor-forming components remain undissolved during slab heating, reducing the inhibitor effect, making secondary recrystallization unstable, and failing to obtain sufficient iron loss characteristics.
[0026] The steel material used in the present invention contains the above-mentioned components, with the balance being Fe and unavoidable impurities. However, in order to improve the iron loss characteristics, the steel material may further contain, in addition to the above-mentioned components, one or more selected from Ni: 0.01-1.50 mass%, Cr: 0.01-0.50 mass%, Cu: 0.005-1.000 mass%, P: 0.005-0.500 mass%, Sb: 0.005-0.500 mass%, Sn: 0.005-0.500 mass%, Bi: 0.005-0.500 mass%, Mo: 0.0010-0.0100 mass%, Nb: 0.001-0.010 mass%, Ta: 0.001-0.010 mass%, and Ti: 0.001-0.0100 mass% as appropriate.
[0027] Next, a method for producing the grain-oriented electrical steel sheet of the present invention will be described. The method for producing a grain-oriented electrical steel sheet of the present invention comprises a series of steps, including heating a steel material (slab) having the above-described composition to a predetermined temperature, hot rolling the same to form a hot-rolled sheet, subjecting the hot-rolled sheet to hot-rolled sheet annealing, cold rolling once or cold rolling at least twice with intermediate annealing in between to form a cold-rolled sheet of a final sheet thickness, subjecting the cold-rolled sheet to decarburization annealing also serving as primary recrystallization annealing, applying an annealing separator to the surface of the steel sheet, followed by finish annealing, and forming an insulating coating. The steps will be described in detail below.
[0028] The above steel material (slab) is preferably produced by melting steel having the above-mentioned composition by a commonly known refining process, and then by a continuous casting method or an ingot casting-blooming rolling method. Thin slabs having a thickness of 100 mm or less may also be produced by a direct casting method.
[0029] Next, the steel slab is heated to a temperature of 1300°C or more and 1400°C or less, and then subjected to hot rolling. If the slab heating temperature is less than 1300°C, the inhibitor-forming components remain in an undissolved state, making secondary recrystallization unstable and making it difficult to obtain sufficient magnetic properties. On the other hand, if the temperature exceeds 1400°C, scale loss increases and surface defects occur. The preferred range is 1310 to 1375°C. The hot rolling conditions are not particularly limited and may be normal conditions for hot rolling grain-oriented electrical steel sheets. In addition, in the case of a thin slab, hot rolling may be omitted.
[0030] Next, the hot-rolled sheet after the hot rolling is subjected to hot-rolled sheet annealing in order to improve the magnetic properties. This hot-rolled sheet annealing may be performed under generally known conditions, and there are no particular limitations.
[0031] Next, the hot-rolled sheet after the above hot rolling is pickled and descaled, and then cold-rolled to a final thickness (product thickness) by one cold rolling or two or more cold rollings with intermediate annealing in between, as is commonly known.
[0032] Next, the cold-rolled sheet having the final thickness is subjected to decarburization annealing, which also serves as primary recrystallization annealing, to obtain a preferred primary recrystallized structure and reduce the C content in the steel sheet to 0.0050 mass% or less at which magnetic aging does not occur. At this time, it is important to rapidly heat the steel sheet at a heating rate of 100 to 1000°C / s between 500°C and 700°C in the heating process of the decarburization annealing in order to improve the primary recrystallized structure and refine the secondary recrystallized grains. If the heating rate is less than 100°C / s, the number of Goss-oriented grains that become the nuclei of secondary recrystallization in the primary recrystallized structure decreases, while if it exceeds 1000°C / s, the number of crystal grains other than Goss-oriented grains increases, and in either case, the magnetic properties decrease. The heating rate is preferably in the range of 150 to 700°C / s. From the viewpoint of promoting decarburization, the decarburization annealing is preferably performed in a moist atmosphere at a temperature of 800 to 900° C. for 60 to 300 seconds.
[0033] Next, the decarburized annealed steel sheet is coated with an annealing separator on the surface of the steel sheet, dried, wound into a coil, and subjected to finish annealing in the coiled state to cause secondary recrystallization. In this case, in the finish annealing, in order to preferentially grow crystal grains in the Goss orientation and suppress the increase of secondary recrystallized grains deviated from the Goss orientation, it is important to gradually heat the steel sheet at a temperature range of 860 to 970°C at a rate of 0.5 to 4.0°C / hr in the heating process. If the heating rate is less than 0.5°C / hr, the orientation sharpness of the Goss orientation in the secondary recrystallized structure decreases, while if it exceeds 4.0°C / hr, the growth rate of the Goss orientation and its neighboring grains increases excessively, and the degree of accumulation of the secondary recrystallized grains in the Goss orientation decreases significantly. The heating rate is preferably in the range of 0.7 to 2.0°C / hr. In order to obtain the above effect, the time for gradually heating the steel sheet at a temperature of 0.5 to 4.0°C / hr as described above needs to be secured for 10 hours or more. The period is preferably 20 hours or more. If the period can be 10 hours or more, the section in which the heating is performed slowly may be a part of the section between 860 and 970° C. The atmosphere in this section is preferably nitrogen, argon, or a mixed atmosphere of nitrogen and argon.
[0034] Following the above-mentioned gradual heating process, in order to eliminate impurities in the steel sheet, the steel sheet is heated to a temperature of 1150 to 1250°C and then subjected to a purification treatment in which the temperature is maintained for 5 to 20 hours. This reduces inhibitor-forming components such as Al, N, S, and Se in the steel sheet to the impurity level. The atmosphere during the purification treatment is preferably hydrogen, but nitrogen or argon can also be used as necessary. The rate of temperature rise up to the purification treatment temperature is preferably 5°C / hr or more. The atmosphere during this treatment can be nitrogen, argon, or a mixture of nitrogen, argon, and hydrogen.
[0035] Next, the steel sheet after the above-mentioned finish annealing has unreacted annealing separator removed from the steel sheet surface, is subjected to planarizing annealing, and is then coated with an insulating coating to obtain a finished sheet. The insulating coating is preferably a tension-imparting insulating coating from the viewpoint of reducing iron loss.
[0036] Furthermore, from the viewpoint of further reducing iron loss, the non-oriented electrical steel sheet of the present invention is preferably subjected to a magnetic domain refinement treatment. As a method for refining the magnetic domain, a conventionally known method can be adopted. For example, in any step after cold rolling, a method of forming grooves on the steel sheet surface by etching or the like continuously or intermittently in a direction intersecting the rolling direction and at predetermined intervals in the rolling direction, or a method of irradiating the steel sheet surface after the insulating coating with an electron beam or a laser beam continuously or intermittently in a direction intersecting the rolling direction and at predetermined intervals in the rolling direction can be adopted. EXAMPLES
[0037] A steel slab containing C: 0.004 mass%, Si: 4.2 mass%, Mn: 0.23 mass%, Al: 0.015 mass%, N: 0.005 mass%, Se: 0.004 mass%, and S: 0.005 mass%, with the balance being Fe and unavoidable impurities, was produced by a continuous casting method. The slab was then heated to a temperature of 1350 ° C, and hot rolled to finish into a hot rolled sheet with a thickness of 2.4 mm. The hot rolled sheet was then subjected to hot rolled sheet annealing at 1100 ° C × 30 seconds, and then subjected to a first cold rolling to an intermediate sheet thickness of 1.8 mm, and then subjected to intermediate annealing at 1020 ° C × 100 seconds, and then subjected to a second cold rolling with a reverse rolling mill to finish into a cold rolled sheet with a final sheet thickness of 0.23 mm. Next, the cold-rolled sheet was subjected to decarburization annealing, which also served as primary recrystallization annealing, at 880°C for 60 seconds in a 50vol%H2-50vol%N2 wet atmosphere. At this time, the heating rate between 500 and 700°C during the heating process was 700°C / s. Next, an annealing separator mainly composed of MgO was applied to the steel sheet surface, and the steel sheet was wound into a coil, after which the steel sheet coil was subjected to finish annealing. At this time, the heating conditions between 860 and 970°C and the annealing atmosphere during the heating process of the finish annealing were changed as shown in Table 3.
[0038] Test pieces were taken from the steel sheets after the final annealing, and the iron loss W 17 / 50 The iron loss (iron loss when excited at 1.7 T at a frequency of 50 Hz) and magnetic flux density B8 (magnetic flux density at a magnetizing force of 800 A / m) were measured by the method described in JIS C 2550. Test pieces were taken from three locations, namely, both ends and the center of the product coil, and the highest (worst) iron loss value and the lowest (worst) magnetic flux density value were taken as representative values for the coil. The results of the above measurements are shown in Table 3 below. From these results, it can be seen that a steel sheet with low iron loss and high magnetic flux density can be obtained when the heating rate in the 860-970°C section of the final annealing is in the range of 0.5-4.0°C / hr.
[0039] [Table 3] EXAMPLES
[0040] Steel slabs having various component compositions shown in Table 4 were manufactured by a continuous casting method. Next, the slab was heated to a temperature of 1200°C, and then hot-rolled to a hot-rolled sheet having a thickness of 2.4 mm. Next, the hot-rolled sheet was subjected to hot-rolled sheet annealing at 1100°C for 30 seconds, and then finished into a cold-rolled sheet having a final thickness of 0.23 mm by the first cold rolling. Next, the cold-rolled sheet was subjected to decarburization annealing, which also served as primary recrystallization annealing, at 880°C for 60 seconds in a moist atmosphere of 50 vol% H2-50 vol% N2. At this time, the heating rate between 500 and 700°C during the heating process was set to 300°C / s. Next, an annealing separator mainly composed of MgO was applied to the surface of the steel sheet, and the steel sheet in a coiled state was subjected to finish annealing. In this case, the heating in the 860-970°C slow heating section was performed in an N2 atmosphere, with heating between 880-940°C at a heating rate of 1.0°C / hr for 60 hours, and the heating rate at other temperatures was 15°C / hr. After that, the temperature was raised to 1180°C at 25°C / hr in a mixed atmosphere of H2:75vol%-N2:25vol%, and purification treatment was performed by holding the temperature for 30 hours in an H2 atmosphere.
[0041] [Table 4]
[0042] Test pieces were taken from the steel sheets after the final annealing, and the iron loss W 17 / 50 The iron loss (iron loss when excited at 1.7 T at a frequency of 50 Hz) and magnetic flux density B8 (magnetic flux density at a magnetizing force of 800 A / m) were measured using the method described in JIS C 2550. Test pieces were taken from three locations, namely, both ends and the center of the product coil, and the highest (worst) iron loss value and the lowest (worst) magnetic flux density value were taken as representative values for the coil. The results of the above measurements are also shown in Table 4. It can be seen from these results that by using a steel material that satisfies the present invention and applying conditions that conform to the present invention, grain-oriented electrical steel sheets with low iron loss and high magnetic flux density can be stably obtained.
Claims
1. A steel material having a composition containing C: 0.002 to 0.10 mass%, Si: 2.0 to 8.0 mass%, Mn: 0.005 to 1.0 mass%, and further containing the following components of group A or B as inhibitor-forming components, with the balance being Fe and unavoidable impurities, is heated to a temperature of 1300°C to 1400°C and hot-rolled to form a hot-rolled sheet, and the hot-rolled sheet is then subjected to a heat treatment. After hot-rolled sheet annealing, the steel sheet is cold-rolled once or cold-rolled twice or more with intermediate annealing to obtain a cold-rolled sheet of the final sheet thickness. The cold-rolled sheet is then subjected to decarburization annealing, which also serves as primary recrystallization annealing. An annealing separator is then applied to the surface of the steel sheet, and finish annealing is performed. In order to form an insulating coating, the steel sheet is rapidly heated at 100 to 1000°C / s between 500 and 700°C in the heating process of the decarburization annealing, and In the heating process of the above-mentioned finish annealing, in the section from 860 to 970 ° C., increasing the temperature at a rate of 0.5 to 4.0 ° C. / hr is called gradual heating, and the above-mentioned gradual heating is performed at least in the section from 900 to 960 ° C. in this method for producing a grain-oriented electrical steel sheet. However, this does not include the case where, in the cooling process after the hot-rolled sheet annealing or the intermediate annealing, the steel sheet is rapidly cooled from 800° C. to 300° C. at an average cooling rate of 200° C. / s or more. Note Group A: Al: 0.010 to 0.050 mass% and N: 0.003 to 0.020 mass% Group B: Al: 0.010 to 0.050 mass%, N: 0.003 to 0.020 mass%, Se: 0.003 to 0.030 mass%, and / or S: 0.002 to 0.030 mass%
2. The steel material further contains, in addition to the above-mentioned component composition, at least one of Ni: 0.01 to 1.50 mass%, Cr: 0.01 to 0.50 mass%, Cu: 0.005 to 1.000 mass%, P: 0.005 to 0.500 mass%, Sb: 0.005 to 0.500 mass%, Sn: 0.005 to 0.500 mass%, Bi: 0.005 to 0.500 mass%, Mo: 0.005 to 0.500 mass%, Nb: 0.0010 to 0.0100 mass%, Ta: 0.001 to 0.010 mass%, and Ti: 0.001 to 0.0100 mass%. The method for producing a grain-oriented electrical steel sheet according to claim 1, characterized in that it contains at least one of the following:
3. 3. The method for producing a grain-oriented electrical steel sheet according to claim 1, further comprising the step of forming grooves in a direction intersecting the rolling direction on the surface of the steel sheet to perform a magnetic domain refinement treatment in any step after the cold rolling.
4. 3. The method for producing a grain-oriented electrical steel sheet according to claim 1, further comprising the step of irradiating the surface of the steel sheet on which the insulating coating is formed with an electron beam or a laser beam in a direction intersecting with the rolling direction to perform a magnetic domain refinement treatment.
Citation Information
Patent Citations
JP1963-008214B
JP1965-015644B
hifunsaibutsushitsuofunsaisurutamenoshindomiru
JP1976013469A
Material of high magnetic flux density one directionally orientated el ectromagnetic steel and its treating method
JP1977024116A
Manufacture of unidirectional silicon steel sheet excellent in magnetic property
JP1983193373A